THE EFFECT OF SNAKE AND LADDER BOARD GAME ON THE ENGLISH LEARNING ACHIEVEMENT OF THE FOURTH GRADE STUDENTS OF ELEMENTARY SCHOOL IN SUKASADA, BULELENG REGENCY IN ACADEMIC YEAR 2015/2016 - ., Dewa Putu Nara Kusuma; ., Dra.Ni Made Ratminingsih, MA; ., Putu Eka Dambayana S., S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Tujuan utama dari penelitian ini adalah untuk meneliti apakah ada efek yang signifikan dari pengguanaan snake and ladder board game terhadap prestasi belajar bahasa Inggris pebelajar anak-anak, terutama siswa-siswi sekolah dasar. Penelitian ini adalah sebuah penelitian eksperimen dengan menggunakan post-test only control group design. Populasi dari penelitian ini adalah semua siswa kelas empat di sekolah dasar Sukasada, kabupaten Buleleng tahun ajaran 2015/2016. Penelitian ini menggunakan teknik cluster random sampling untuk memilih sampel. Ada dua kelas yang terpilih sebagai sampel, SD Negeri 2 Sukasada sebagai kelompok kontrol dan SD Negeri 3 Sukasada sebagai kelompok eksperimen. Data dianalisis menggunakan analisis statistik deskriptif dan inferensial. Hasil-hasil memperlihatkan bahwa rata-rata dari kelompok kontrol yang diajar mengguanakan teknik konvensional adalah 79.6 dan rata-rata dari kelompok eksperimen yang diajar menggunakan snake and ladder board game adalah 84.1. Hasil dari penghitungan sampel independen t-test menunjukan nilai dari tobs (t observation) adalah 4.791 dimana tcv (t critical value) dalam signifikansi alfa 0.05 (5%) dan tingkat kebebasan 62 adalah 1.998. Dapat disimpulkan bahwa snake and ladder board game memberikan efek yang signifikan terhadap prestasi belajar bahasa Inggris siswa kelas empat sekolah dasar di Sukasada, Kabupaten Buleleng tahun ajar 2015/2016.Kata Kunci : Prestasi belajar bahasa Inggris, snake and ladder board game, pebelajar anak-anak The main purpose of this research is to investigate whether there is any significant effect of snake and ladder board game on young learners’ English learning achievement, especially the fourth grade students of elementary school. This research was an experimental research using post-test only control group design. The population of this study was 103 fourth grade students of elementary school in Sukasada, Buleleng regency in academic year 2015/2016. This research used cluster random sampling technique to choose the samples. There were two classes as the samples, SD Negeri 2 Sukasada as the control group and SD Negeri 3 Sukasada as the experimental group. The data were analyzed by using descriptive and inferential statistic analysis. The results showed that the mean score of control group that was taught by conventional technique was 79.6 and the mean score of experimental group that was taught by snake and ladder board game was 84.1. The result of the independent sample t-test calculation showed the value of tobs (t observed) was 4.791 where the tcv (t critical value) in alpha significance 0.05 (5%) and the degree of freedom 62 was 1.998. It could be inferred that the tobs (t observed) was higher than the tcv (t critical value). It can be concluded that snake and ladder board game gives the significant effect on students’ English learning achievement of the fourth grade students of elementary school in Sukasada, Buleleng regency in 2015/2016 academic year.keyword : English learning achievement, snake and ladder board game, young learners